From hypereosinophilia to hypereosinophilic syndrome: real-world application of a two-tailed approach for HES diagnosis - Nicola, Stefania; Borrelli, Richard; Ridolfi, Irene; Lo Sardo, Luca; Negrini, Simone; Fornero, Monica; Rashidy, Nicolò; Corradi, Federica; Badiu, Iuliana; Cerutti, Eleonora; Costanzo, Giulia; Del Giacco, Stefano; et al. (Frontiers in Immunology, 2026)
BackgroundHypereosinophilic Syndrome (HES) is a rare disorder with a heterogeneous clinical presentation. If not recognized, it can lead to diagnostic delay and worse prognosis. Our study aimed to describe the real-world scenario of patients presenting with hypereosinophilia (HE), diagnosed with HES in an Italian Immunology Excellence University Centre. In addition, we also assessed the feasibility of a two-tailed approach for HES diagnosis, which consists of proceeding from the beginning with the differential diagnosis and systematic evaluation of organ damage.MethodsA retrospective observational single-center study was conducted. All patients underwent blood and instrumental tests to simultaneously identify HES etiology and any organ damage, through a process we called the “two-tailed approach”.ResultsTwo hundred forty-seven patients with HE referred to our center underwent the two-tailed approach. Due to either the presence of a straightforward underlying disease associated with HE, or the lack of sustained hypereosinophilia, 168 patients (68.0%) were excluded from the study. Seventy-nine patients (31 females, 39.2%) with a mean age of 54.9 years were finally diagnosed with HES. 19 (24.1%) patients were diagnosed with reactive HES, 15 (19.0%) with overlap HES, 1 (1.3%) with myeloid-HES, 10 (12.7%) with lymphocytic HES, and 8 (10.1%) with idiopathic HES. Sixty-three patients showed involvement of at least two organs: the lung (32/63, 50.7%), the skin (24/63, 38.1%), the bowel (23/63, 36.5%), and the peripheral nervous system (25.4%). Eight patients (8/63, 12.7%) showed heart involvement. The diagnosis was achieved in 4 ± 1.8 months, and no deaths were observed.ConclusionHE is a common reason for consultations with allergists and clinical immunologists, and the two-tailed approach, which tests simultaneously for diagnosis and organ damage, should be implemented from the initial evaluation of patients with HE. The lower rate of idiopathic HES diagnosis and the higher frequency of heart involvement we found confirm the usefulness of the tool in reducing the risk of mistakes in classifying HES subtypes and the diagnostic delay, thus allowing prompt and tailored treatment and better outcomes.